Türkiye’de yönetimsel aklın inşası : aile şûrası raporlarının eleştirel bir analizi - Tuzcuoğlu, Beyhan Çağrı (My University, 2022)
Bu tezin amacı Türkiye’de neoliberal yönetimsel aklın inşası sürecini analiz etmektir. 1990-2014 yılları arasında gerçekleştirilen altı Aile Şurası’nın kararları üzerine yapılan söylem analiziyle Foucault’nun neoliberal yönetimsellik olarak adlandırdığı yeni yönetim aklı ve tekniklerinin Türkiye’de nasıl adapte edilmeye çalışıldığı incelenmiştir. Bu söylemlerle pratikte uygulanan politikalar ve iktidar mekanizmalarının bağlantıları gösterilmiş, Türkiye’nin neoliberalleşme süreci Foucaultcu bir perspektifle ele alınmıştır.

Aim of this thesis is to analyze the process of construction of neoliberal governmental reason in Turkey. By a discourse analysis on reports of six Family Councils made between 1990-2014, it was examined that how a new governing reason and techniques, which are defined as neoliberal governmentality by Foucault, were tried to be adapt in Turkey. Connection between these discourses and policies and power mechanisms were shown and Turkey’s neoliberalization process was discussed with a Foucauldian perspective.
Construction of governmental reason in Turkey : a critical analysis of family council reports
Keywords: Aile Şuraları; Family Councils; İktidar mekanizmaları Governmentality; Neoliberalism; Neoliberalizm; Politics and government; Power Mechanisms; Siyaset ve yönetim; Turkey; Türkiye; Yönetimsellik